Do you want to know who anastasia candre is? dear reader, here i am (2014)
This autobiographic text by Anastasia Candre was composed from several unpublished sources in Spanish and Witoto, and excerpts from published sources. It is divided into eight parts. In the first part, she tells about her childhood, her learning process with her parents and siblings, and her entrance into the indigenous boarding school in La Chorrera. In the second part, she narrates about her arrival to Leticia, the jobs she did, and her completion of secondary school. In the third part, she relates about the time she spent in Universidad Nacional de Colombia as a student of linguistics. In the fourth part, she speaks about her research of the songs of the ritual of the fruit and her encounter with the elder Jimuizɨtofe. In the fifth part, she tells a about her activities as a singer and dancer and includes images of her presentations. In the sixth part, she refers to her work as a painter and includes images of several of her paintings. In the seventh part, she tells about her incursions into poetry, and includes two published and one unpublished poem. In the eighth part, she speaks about her dreams and concludes with an unpublished poem. The text also contains a list of Anastasia’s trajectory: awards, publications, reports, exhibitions and presentations, teaching activities.